Spinal Muscular Atrophy in Blonde D'Aquitaine Calves Is Not Associated With FVT1 Gene Mutation - Cagnotti, Giulia; Cantile, Carlo; Chessa, Stefania; Sacchi, Paola; D'Angelo, Antonio; Bellino, Claudio (Frontiers in Veterinary Science, 2020)
Spinal muscular atrophy (SMA) is a motor neuron disease (MND) in humans and diverse animal species: canid, felid, and bovid. To date, bovine SMA has been reported in Brown Swiss, Holstein, Friesian, and Red Danish breed; it has been associated with a genetic mutation of the FVT1 gene, also known as 3-ketodihydrosphingosine reductase (KDSR). The aim of the present case series was to describe clinical presentation, pathological findings, and genetic analysis of five Blond d’Aquitaine calves diagnosed with SMA and to determine whether the mutation was associated with the disease. Five Blonde d’Aquitaine calves (3 females and 2 males) from the same cow-calf operation farm were presented between June 2018 and February 2019 because unable to stand or walk unassisted since birth. Neurological examination aroused suspicion of a diffuse lesion affecting the peripheral nervous system in all calves. Findings from electromyographic investigations and muscle and nerve biopsies were consistent with a non-regenerative, chronic, active axonal neuropathy and marked neurogenic muscular atrophy and assumed to be associated with a neurodegenerative process. Histopathological examination of tissue samples from two animals revealed neuronal loss and several degenerated, shrunken and hypereosinophilic neurons at the level of the ventral horn of the cervico-thoracic and the lumbo-sacral intumescence, diffuse loss of myelinated axons at the level of the ventral funiculi of all segments of the spinal cord, and moderate diffuse astrocytic reaction. These findings confirmed the diagnosis of SMA. No mutation of the FVT1 gene was found on genetic analysis. Further study into the causative gene mutation of SMA in Blonde D’Aquitaine calves is under way. Identification of a novel genetic mutation could improve our understanding of the disease in human medicine.